Lipase member H is a downstream molecular target of hypoxia inducible factor-1α and promotes papillary thyroid carcinoma cell migration in BCPAP and KTC-1 cell lines - Li, Yuefeng (Cancer Manag Res, 2019)
BACKGROUND: Papillary thyroid carcinoma (PTC) is the most common type of thyroid carcinoma, which is associated with a high incidence of lymph-node metastasis. Multiple biomarkers have been identified for the precise diagnosis of PTC at an early stage. However, their role in PTC remains poorly elucidated. Previously, we reported that lipase H (LIPH), a membrane-bound protein, was highly expressed in PTC. This study aimed to fully elucidate the causal role of LIPH in the development of PTC and investigated its relationship with lymph-node metastasis in PTC. MATERIALS AND METHODS: Quantitative reverse transcription PCR and immunohistochemistry were used to measure the mRNA and protein expression levels of LIPH in 45 and 6 pairs of PTC tissues and adjacent normal tissues, respectively. Clinical tissue data of 504 PTC tissues and 60 normal thyroid tissues from The Cancer Genome Atlas database were used to analyze the correlation between LIPH expression level and clinical features in PTC. siRNAs were used to knock down genes, while plasmids were used to overexpress genes. Two PTC cell lines (KTC-1 and BCPAP) were used in subsequent cytological function studies. In addition, a hypoxia stress model was constructed using cobaltous chloride hexahydrate reagent, and the protein expression level of the corresponding biomarkers was measured by Western blotting. RESULTS: This study revealed that high expression of LIPH in PTC was closely associated with lymph-node metastasis. Our cellular function experiments indicated that LIPH positively correlated with the malignant behavior of PTC cell lines. We further confirmed the role of LIPH in hypoxia and its relationship with the epithelial–mesenchymal transition pathway in PTC. CONCLUSION: LIPH plays an important role in PTC oncogenesis and development, especially in lymph-node metastasis. It can be regarded as a biomarker for the diagnosis and treatment of PTC in the near future.